O nível de Inteligência Emocional e o desempenho acadêmico de alunos de Medicina - ALMEIDA, M. A. (2019)
The objective of this study was to evaluate the level of emotional intelligence and the correlation with the academic performance of 76 medical students in a private institution in the south of Minas Gerais, Brazil. The study was based on a cross section in which two self-fulfilling data collection instruments were used, one for the collection of socio-demographic and academic data of the students and another for the evaluation of the level of emotional intelligence based on the TAIES Scale Schutte Self Report EI scale Test. The data were correlated with the academic performance obtained directly from the students' academic records during the periods already studied and the referred scores obtained in the evaluations, with calculation of the general average, provided by the educational institution. This pointed to a non-correlation between the variables, confirming the null hypothesis. In addition, in the theoretical field, the study investigated the development of the definition of emotional intelligence as an autonomous ability and the last studies of impact on the subject point to the perspective that the concept of emotional intelligence has no conceptual independence, as one of the aspects of social intelligence, a broader construct.